Immunohistochemical Evaluation of β-catenin Marker in Papillary Thyroid Cancer Clinicopathologic Behavior - Katayoun Ziari; Mojgan Sanjari; Moeinadin Safavi (Iranian Society of Pathology, 2018)
Background & objective: papillary thyroid cancer is the most common cancer of thyroid accounting for 75%-85% of all thyroid malignancies. Recently, β-catenin has been determined to play a role in clinical course of human epithelial cancers. This study was designed to reveal the association of β-catenin marker and papillary thyroid carcinoma behavior. Methods: 63 paraffin blocks of papillary thyroid carcinoma were stained with ready to use monoclonal β-catenin antibody according to manufacturer's instructions. Memberanous, cytoplasmic and nuclear staining was scored according to intensity of immunoreactivity. β-catenin immunostaining association with clinical parameters like number of recurrences and cumulative dose of radioiodine therapy were analyzed using SPSS version 15. Histopathologic parameters like tumor stage, grade, capsular invasion, lymphovascular invasion, lymph node involvement, distant metastasis and other variables were also evaluated for association with β-catenin immunoreactivity Results: 77.8% of papillay thyroid carcinoma were well differentiated and the remaining were poorly differentiated. Loss of β-catenin membrane immunostaining depicted correlation with number of recurrences (p=0.023% , Pearson correlation= -0.285). Its loss of memberanous staining correlated similarly with cumulative dose of radioiodine (p= 0.046, Pearson correlation = -0.253). Loss of membranous β-catenin was significantly associated with some histopathologic findings like nodal involvement (p<0.001), distant metastasis (p=0.003) and tumor dedifferentiation (p< 0.001). Conclusion: Loss of β-catenin membranous staining and its cytoplasmic accumulation were associated with aggressive clinicopathologic behavior. The exact effect of radioiodine exposure on β-catenin pathway remained to be determined in future.